Mesoscopic study on fracture behavior of fully graded concrete under uniaxial tension by using the phase-field method. (September 2022) - Guo, Jinjun; Lin, Weiqi; Qin, Xiangnan; Xu, Yaoqun; Dong, Kang
Highlights: The meso-mechanical model of fully-graded concrete is established with mesh-mapping and geometry-partitioning. The influence of loading time, mesoscale structure and mesh scheme is studied for application of the phase field method in mesoscopic concrete. The feasibility and validity of the phase field method is verified with numerical simulation of fully-graded concrete under uniaxial tension. Abstract: The applicability and rationality of the phase-filed method are systematically analyzed for utilization in mesoscopic study on fully graded concrete under uniaxial tension. In this study, two kinds of mesoscopic models for fully graded concrete are generated by the polygonal characteristic parameter transformation method, and their complicated mechanical response and fracture behavior are investigated using the phase-filed method. Numerical simulations of uniaxial tensile experiments are conducted to study the effects of step time, element parameters, and meso-structures on the crack propagation and fracture mechanical response of fully graded concrete. Moreover, the computational efficiency and convergence of the phase-field method are systematically analyzed using various model setup. It is found that the numerical results of stress–strain curves and crack propagation paths are both in good agreement with the experimental results and the output from the distributed cohesive element method, and phase-field method demonstrates advantages in numerical stability. The accuracy and efficiency of this approach, which combines phase-field method and random polygonal aggregate models, are tested to study the fracture behavior of fully graded concrete.